"Friend-ish": Home Care Workers, "Social Labor" and Managing the Boundaries of the Carer Relationship. (April 2023) - Lam, Jack; Baxter, Janeen
We examine how changes in home care work, with greater emphasis on social support, have led to corresponding changes in the forms of labor performed by home care workers. Drawing on interviews with fifty older adults, we find in addition to physical and emotional labor, workers may be increasingly expected to engage in a form of labor we term "social labor, " in which they actively manage the boundary between the professional services they provide and the personal relationships that may develop. We find examples of such expectations include (1) following the lead of clients who set out terms of the relationship and degree of sociality, (2) managing the potential dual role of "support worker" and "friend, " and (3) meeting social needs of clients vulnerable to isolation. As Government acknowledges the value of social support and companionship, greater attention is needed to this aspect of care work, with implications for workers and clients.